1997
DOI: 10.4319/lo.1997.42.5.1001
|View full text |Cite
|
Sign up to set email alerts
|

The origin of sedimenting detrital matter in a coastal system

Abstract: Total sedimentation and the fraction due to copepod fecal pellets were measured during the growth season (March–October 1989) in the southern Kattegat, Denmark. In this period the sedimentation of detritus made up 52 g C m−2, equal to 82% of the sedimenting matter from the euphotic zone, but fecal pellets (11 g C m−2) constituted only a minor fraction. The remaining detrital matter was produced by other heterotrophs than copepods. Published data on heterotrophic biomass and grazing obtained during the investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…This is the lowest value reported. By comparison, in the Kattegat (Lundsgaard and Olesen 1997), in the Norwegian Sea (Bathmann et al 1987), and on the Japanese coast (Sasaki et al 1988), fecal pellets contributed to 4-20% of particulate organic carbon sedimentation. Apparently, the special characteristics of the coastal northern Baltic Sea, i.e., steep hydrographical stratification, potential dominance of athecate flagellates and protozoans in the diet of copepods, and especially the dominance of small copepods, all make this area an extreme case in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…This is the lowest value reported. By comparison, in the Kattegat (Lundsgaard and Olesen 1997), in the Norwegian Sea (Bathmann et al 1987), and on the Japanese coast (Sasaki et al 1988), fecal pellets contributed to 4-20% of particulate organic carbon sedimentation. Apparently, the special characteristics of the coastal northern Baltic Sea, i.e., steep hydrographical stratification, potential dominance of athecate flagellates and protozoans in the diet of copepods, and especially the dominance of small copepods, all make this area an extreme case in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…In Disko Bay, heterotrophic dinoflagellates were estimated to graze 7-18% of the diatom bloom. Using the same data for the Kattegat as presented in this paper, Lundsgaard and Olesen (1997) suggested that heterotrophic dinoflagellate ingestion was 21% of the spring bloom primary production. By comparison, the potential grazing of copepods during the same period was 20 to Ͼ100% (Disko; Madsen et al 2001) and 8% (Kattegat; Lundsgaard and Olesen 1997) of the primary production.…”
Section: ϫ2mentioning
confidence: 99%
“…Although fecal pellet in some cases constitute a significant fraction of the sedimenting organic carbon , Landry et al 1994, they typically contribute less to the sedimentary flux than other sources (Fowler et al 1991, Wassmann et al 1999, Roy et al 2000. Accordingly, many studies report low contributions from fecal pellets to the lower ocean proper (Bathmann et al 1987, Lane et al 1994, Lundsgaard & Olesen 1997 even with high secondary production in the euphotic zone (Ayukai & Hattori 1992, Viitasalo et al 1999. However, the significance of zooplankton fecal pellets extends well beyond the question of carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%